2019
DOI: 10.1017/s0959269519000188
|View full text |Cite
|
Sign up to set email alerts
|

Texting the future in Belgium and Québec: Present matters

Abstract: This study investigates the variation in the expression of Future Temporal Reference in text messages in Belgian and Québécois French. Three variants are considered: the Futurate Present, the Synthetic Future and the Analytic Future. The results of multivariate analyses show that the use of the Futurate Present does not appear to be subject to dialectal variation: both communities use this variant at similar rates, and the use of the variant is constrained by the same linguistic factors. The two dialects show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
(104 reference statements)
0
5
0
3
Order By: Relevance
“…Two recent studies offer further evidence to support this hypothesis: Côté (2018) and Tremblay et al (2019). Côté (2018) looks at FTR in L2 French.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Two recent studies offer further evidence to support this hypothesis: Côté (2018) and Tremblay et al (2019). Côté (2018) looks at FTR in L2 French.…”
Section: Discussionmentioning
confidence: 87%
“…The authors attribute this to learners' earlier exposure to, and thus greater familiarity with, these two verbs, as well as to their high frequency overall. In their study of FTR in text messages, Tremblay et al (2019) also found that verb type was a significant factor, with avoir, être and modal verbs being much more likely to appear with IF. 23 They argue that this is related to morphological complexity: the more irregular the paradigm, the more likely the use of IF.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations